MENGENAL IDDSI (INTERNATIONAL DYSPHAGIA DIET STANDARDISATION INITIATIVE) MODIFIKASI TEKSTUR MAKANAN UNTUK DISFAGIA: LITERATUR REVIEW - Wawang Suswan; Listiyani Eka Tyastuti; Meika Rahmawati Arifah (JOURNAL HEALTH AND NUTRITIONS, 2026)
The modification of food and beverage textures represent a safe and efficacious means to ensure the nutrition requirements of patients with dysphagia. However, there are discrepancies between countries in regard to the standards and levels of texture modification diets. In 2015, the International Dysphagia Diet Standardisation Initiative (IDDSI) was introduced, comprising standardised terminology and definitions for the description of Texture-Modified Food (TMF) and Thickened Fluid (TF) for individuals with dysphagia. The use of IDDSI as a universal terminology of TMF and TL among countries to prevent confusion of fluid/food levelling identification. IDDSI employs three descriptors to identify the level texture modification, comprised of number, colour, and label. There were eight levels of IDDSI (level 0-7) for both TMF and TF. The IDDSI measurement system employs a range of easy to access instruments, including spoons, forks, chopsticks, syringes, and fingers. IDDSI has been adopted by countries in Asia, but Indonesia has not implemented IDDSI. Indonesia traditional food and beverages, such as bubur sumsum or hospital enteral formula can be measured easily with IDDSI framework. Thus, there was opportunity to adopt IDDSI framework for assessing Indonesian food. Further research is required, particularly within the context of hospital food services and should aim to describe the level of hospital foods and beverages based on IDDSI, and to develop thickeners utilising traditional ingredients for enhancing nutrition care of people with dysphagia.Modifikasi tekstur makanan dan minuman merupakan cara untuk memenuhi kebutuhan gizi dalam pengelolaan disfagia secara aman. Namun terdapat perbedaan di beberapa negara mengenai standar serta tingkatan dalam modifikasi tekstur diet. The International Dysphagia Diet Standardization Initiative (IDDSI) mulai diperkenalkan pada tahun 2015, berisi tentang terminologi standar dan definisi untuk menggambarkan modifikasi tekstur makanan dan minuman untuk pasien disfagia. IDDSI dapat digunakan sebagai standar universal untuk menghindari kebingungan akibat perbedaan level dan penamaan di tiap negara. Ada 3 indikator untuk mengidentifikasi tingkatan tekstur diet dalam IDDSI yaitu nomor, warna, dan label, dikelompokkan menjadi delapan level (level 0-7) untuk tekstur makanan modifikasi dan kekentalan cairan. Pengukuran IDDSI menggunakan alat sederhana yaitu sendok, garpu, sumpit, syringe serta jari tangan. IDDSI sudah diadopsi oleh banyak negara di Asia, namun saat ini belum ada penerapan kerangka kerja IDDSI dalam pengelolaan disfagia di Indonesia. Beberapa makanan dan minuman seperti bubur sumsum dan formula enteral Rumah Sakit (RS) dapat diukur menggunakan kerangka kerja IDDSI. Hal ini menggambarkan adanya peluang untuk mengadopsi kerangka kerja IDDSI pada makanan dan minuman yang umum di Indonesia. Perlu penelitian lebih lanjut dalam menggambarkan level makanan dan minuman standar RS sesuai kerangka kerja IDDSI serta pembuatan pengental dengan bahan tradisional untuk meningkatkan asuhan gizi dan pelayanan makan disfagia.